Demographic Insights into Migraine Prevalence and a Cost-Effective Analysis of Various Prophylactic Medications - Divya Saran; Lokendra Sharma; Alka Bansal; Susheel Kumar; Rajveer Singh Rathore; Priyanka Joshi (Journal of Pharmaceutical Research)
Headache, a common human experience, has been classified since antiquity. Migraine, a prevalent disabling primary headache condition, has significant personal and societal consequences. Understanding its demography is critical for creating effective prevention and treatment methods. An observational study of 387 persons with chronic migraine was conducted over a six-month period. They were divided into three groups and given a separate prophylactic drug. Demographic information was collected at the outset, and patients were assessed at 4, 8, and 12 weeks. The study population had an average age of 38.20 ±12.78 years, with 90% of the participants being female. Migraine was most common in those under 30 (37%), followed by those between 31 and 40 (28%). The most common co-morbidity (43.5%) was anxiety. Propranolol alone was the most cost-effective preventative medication, followed by propranolol plus escitalopram. This study sheds light on the intricate relationship between migraine and demographic characteristics, underlining the significance of individualized care. Because females are more vulnerable, age-specific therapies are critical, as are gender-sensitive approaches. The potential benefits of preventative drugs in decreasing both personal and society burdens are highlighted by socioeconomic factors and cost-effectiveness analyses. To optimize outcomes and cost allocation, this study advocates for a patient-centered, comprehensive approach to migraine care. Keywords Migraine, Prevalence, Prophylactic Medications, Demographics, Costeffectiveness Analysis